Analisis Usaha Drclth (Doctor Clothes) Solusi Busana Terjangkau yang Authentic - Rahma Dianti, Annisa (Jurnal Etnik: Ekonomi-Teknik, 2023)
This Research was motivated by the height the influence of the East Asian Entertainment Industry, especially Korea, on the local community, which made Indonesian women’s clothing styles begin to shift, following hallyu or Korean Fashion Trend which brought a tremendous increase Creative Business Opportunities, a stalemate in the domestic market Fashion industry.The aim of this research is to find out environmental analysis business and business Feasibility Analysis of DrClth’s Business. This research uses descriptive analysis with a business plan approach. Research result in the form of analysis, business environment, carried out by assessing the marketing aspect, the production aspect, the memories aspect and the source aspect, with the result that DrClth business has good potential in the fashion Industry sector, while the business feasibility analysis is carried out by calculating analysis, financial analysis of business feasibility, exploring business sustainability, calculating the bares of sales and break event point.The conclusion of this study is that DrClth results are feasible carried out, based on the analysis of the business environment and business feasibility analysis that has been carried.